Effect of resveratrol supplementation on lipid metabolism in healthy and obese cats - Yun, Jung Eun; Kang, Seung Rok; Kim, Jae Young; Kim, Hyun Joong; Kobayashi, Motoo; Arai, Toshiro (Frontiers in Veterinary Science, 2025)
IntroductionThe prevalence of lipid metabolism disorders, including obesity, increases with age in cats and humans. Obesity is a condition characterized by systemic low-grade inflammation and oxidative stress caused by excessive visceral fat accumulation. Resveratrol (RSV), a natural plant polyphenol, modulates the expression of anti-inflammatory factors. This study aimed to investigate the effects of resveratrol supplementation on lipid metabolism in both healthy and obese cats and assess its potential as a dietary supplement for improving lipid metabolism disorders in this population.MethodsPlasma metabolite and hormone concentrations, and enzyme activities were measured in healthy, obese, and overweight cats supplemented with RSV for 4 weeks. RVS was supplemented at 1 mg/kg body weight/day (low dose) and 5 mg/kg/day (high dose) in capsules for 4 weeks.ResultsBody weight, body condition score, BUN, and insulin concentrations did not change in obese or overweight cats with RSV supplementation for 4 weeks. Plasma triglyceride, free fatty acids, and serum amyloid A (SAA) concentrations and lactate dehydrogenase (LDH) activities decreased, and adiponectin concentrations increased markedly in obese and overweight cats after RSV supplementation.DiscussionDecreased plasma SAA concentrations and LDH activities and increased plasma adiponectin concentrations in obese and overweight cats seem to be induced by the improvement in liver function and the anti-inflammatory effect of RSV. Moreover, RSV supplementation may be useful in treating lipid metabolism disorders, including obesity, in cats.